Kehidupan Anak Pengamen Jalanan di Simpang Pos Jl. Jamin Ginting Kelurahan Kwala Bekala Medan - Ridawati Bangun; Supsiloani Supsiloani (Jurnal Antropologi Sumatera, 2023)
This study purpose to know some factors which has background a children working as a singer, social interaction between a children singers with the condition economy of family. The children working as a singer in Simpang Pos Jl. Jamin Ginting Kelurahan Kwala Bekala Medan. The research methodology used a qualitative research with descriptive approach technic to collecting data that used is observation, interview, and documentation. The result of research is the children that working as singers has background some of factors related to one another is a problem of poverty that cause low income the parents so that the children working too, some of the poor children working because willingness their self because realize the income of their parents that unable sufficient the needed of family, beside that the children working in the streets as singers that cause of blind following factors with their friend of the same age and cultural factors.